The E3 ubiquitin ligase HectD3 attenuates cardiac hypertrophy and inflammation in mice - Rangrez, Ashraf Yusuf; Borlepawar, Ankush; Schmiedel, Nesrin; Deshpande, Anushka; Remes, Anca; Kumari, Manju; Bernt, Alexander; Christen, Lynn; Helbig, Andreas; Jungmann, Andreas; Sossalla, Samuel; Tholey, Andreas; et al. (Communications biology, 2020)
Myocardial inflammation has recently been recognized as a distinct feature of cardiac hypertrophy and heart failure. HectD3, a HECT domain containing E3 ubiquitin ligase has previously been investigated in the host defense against infections as well as neuroinflammation; its cardiac function however is still unknown. Here we show that HectD3 simultaneously attenuates Calcineurin-NFAT driven cardiomyocyte hypertrophy and the pro-inflammatory actions of LPS/interferon-γ via its cardiac substrates SUMO2 and Stat1, respectively. AAV9-mediated overexpression of HectD3 in mice in vivo not only reduced cardiac SUMO2/Stat1 levels and pathological hypertrophy but also largely abolished macrophage infiltration and fibrosis induced by pressure overload. Taken together, we describe a novel cardioprotective mechanism involving the ubiquitin ligase HectD3, which links anti-hypertrophic and anti-inflammatory effects via dual regulation of SUMO2 and Stat1. In a broader perspective, these findings support the notion that cardiomyocyte growth and inflammation are more intertwined than previously anticipated.